Preparation method of self-repairing epoxy vitreous body material and prepared material
By introducing exchange reactions between DA bonds, ester bonds and disulfide bonds into epoxy resin materials, an epoxy vitreous material with self-healing ability in the range of 80-160°C was prepared, and the existing materials were solved Repairing the problem of narrow temperature range has achieved multiple repairs of materials and improved mechanical properties.
Patent Information
- Application Number
- CN202411832121.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The self-repair temperature range of existing epoxy resin materials is narrow, making it difficult to achieve multiple repairs at different temperatures, which limits its application range.
By carrying out specific reactions of epoxy resin copolymer, modification curing agent and organic acid catalyst, a self-healing epoxy vitreous material is prepared. This material has self-healing ability in the range of 80-160°C and passes through DA The exchange reaction of bonds, ester bonds and disulfide bonds achieves multiple repairs of the material.
It realizes the multiple repair capabilities of self-healing epoxy vitreous materials, with short repair time, wide repair response temperature range, and excellent mechanical properties, and is suitable for a wide range of application scenarios.
Smart Images

Figure CN119431739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of epoxy glass materials, and in particular to a preparation method of a self-repairing epoxy glass material and the prepared material. Background Art
[0002] Epoxy compounds have excellent mechanical properties and electrical insulation properties and are widely used in various fields. However, damaged epoxy resins are often difficult to repair and difficult to degrade after being discarded, causing great resource and environmental problems.
[0003] When self-healing polymers and composite materials based on dynamic covalent bonds are damaged, the materials are repaired through the reversible breaking and recombination of chemical bonds. Compared with external aid self-healing materials, dynamic covalent bond self-healing materials have the significant advantage of multiple repairs; compared with non-covalent bond self-healing materials, the mechanical strength is significantly improved, so the application range is also wider. Diels-Alder reaction (DA reaction), disulfide bond and ester bond are common dynamic covalent bonds. DA reaction is a thermally reversible dynamic chemical reaction, that is, the conversion between the forward and reverse reactions is achieved by changing the temperature. The reaction conditions are mild and no catalyst is required. Based on the characteristics that the disulfide bonds in epoxy resins are easily broken to form sulfur free radicals and thiol groups, and disulfide bond exchange is achieved through oxidation reactions, the disulfide exchange reaction can be triggered by various stimuli such as heat, light and external free radicals, and is very popular in the design of self-healing and recyclable networks. Ester bonds can undergo ester exchange reactions under the action of catalysts, and the response temperature is relatively high (for example, several hours at 150°C or a few minutes at 240°C). Under the action of external forces, the ester bonds in the cross-linked network will break and regenerate, so that the original covalent cross-linked network is in dynamic equilibrium, so that the material can be reshaped into other shapes. At present, there is no material that has the self-healing function of the above three thermally reversible bonds at the same time.
[0004] Therefore, expanding the repair response temperature range of intrinsic self-healing materials is an urgent issue that needs to be addressed, which is of great significance to the promotion and application of intrinsic self-healing materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of narrow self-repairing temperature range of existing epoxy resin materials, and to provide a method for preparing a self-repairing epoxy glass material and the prepared material, which has strong self-repairing ability, short repair time, wide repair response temperature range, and excellent mechanical properties.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a self-repairing epoxy glass material, characterized in that the preparation method comprises: subjecting an epoxy resin copolymer, a modified curing agent and an organic acid catalyst to a first reaction, wherein the molar ratio of the epoxy resin copolymer to the modified curing agent is 2:0.5-5, and the molar ratio of the organic acid catalyst to the epoxy resin copolymer is 1-10:20.
[0007] Preferably, the first reaction process comprises: mixing the epoxy resin copolymer and an organic acid catalyst to obtain a resin mixture;
[0008] The modified curing agent is added to the resin mixture and reacted at 60-100° C. for 0.5-2 hours, and then the temperature is raised to 130-180° C. and the reaction is continued for 1-3 hours.
[0009] After adding the curing agent, a cross-linking reaction will occur between the resin mixture and the modified curing agent. The initial reaction temperature of the cross-linking reaction can be 60°C, 70°C, 80°C, 90°C, 100°C, etc., and the time can be 0.5h, 1h, 1.5h, 2h, etc. The temperature of the continued reaction can be 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., and the time can be 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0010] In some embodiments, preferably, the organic acid catalyst is anhydrous zinc acetate.
[0011] In some embodiments, preferably, the molar ratio of the epoxy resin copolymer to the modified curing agent is 2: 1. The molar ratio of the epoxy resin copolymer to the modified curing agent is directly related to the mechanical properties of the material after self-healing, and the molar ratio of the two can be 2: 0.5, 2: 1, 2: 1.5, 2: 2, 2: 3, 2: 4, 2: 5, etc.
[0012] The molar ratio of the organic acid catalyst to the epoxy resin copolymer can be 1:20, 2:20, 3:20, 4:20, 5:20, 8:20, 10:20, etc.
[0013] In some embodiments, preferably, the mixing temperature is 100-110° C. and the mixing time is 0.5-2 h. The purpose of mixing is to completely dissolve the organic acid catalyst, and the mixing temperature can be 100° C., 105° C., 110° C., etc., and the mixing time can be 0.5 h, 1 h, 1.5 h, 2 h, etc.
[0014] In some embodiments, preferably, the resin mixture is cooled to the reaction temperature before adding the modified curing agent to react. After cooling and adding the modified curing agent and stirring evenly, vacuum stirring can be further performed to remove bubbles.
[0015] In some embodiments, preferably, the method for preparing the epoxy resin copolymer comprises: subjecting an epoxy resin monomer and furfurylamine to a third reaction to obtain the epoxy resin copolymer.
[0016] In some embodiments, preferably, the preparation method of the epoxy resin copolymer comprises: performing a second reaction on an epoxy resin monomer and suberic acid in the presence of a quaternary ammonium salt catalyst to obtain an epoxy-terminated β-hydroxy ester-containing epoxy resin;
[0017] The β-hydroxy ester-containing epoxy resin is dissolved in a first solvent, and furfurylamine is added to carry out a third reaction, and the first solvent is removed to obtain an epoxy resin copolymer.
[0018] The present invention has no special requirements for the specific type of epoxy resin monomer. For example, the epoxy resin monomer can be any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, 1,6-hexanediol diglycidyl ether and resorcinol diglycidyl ether, or other types of epoxy resin monomers.
[0019] Furfurylamine, also known as 2-furylamine, has a chemical formula of C5H7NO.
[0020] There is no particular requirement for the type of the first solvent, as long as it can dissolve the β-hydroxy ester epoxy resin and furfurylamine and does not react with the raw materials. For example, the first solvent can be toluene.
[0021] The process of removing the first solvent includes: placing the product obtained by the third reaction in a rotary evaporator, and rotary evaporating until no liquid drops, and the remaining product is the epoxy resin copolymer.
[0022] In some embodiments, preferably, the molar ratio of the epoxy resin monomer to suberic acid is 10:0.1-5.
[0023] In some embodiments, preferably, the molar ratio of the epoxy resin monomer to suberic acid is 10:2.
[0024] The molar ratio of the epoxy resin monomer and suberic acid is directly related to the mechanical properties of the material after self-healing. The molar ratio of the two can be 10:0.1, 10:1, 10:2, 10:3, 10:4, 10:5, etc.
[0025] In some embodiments, preferably, the molar ratio of furfurylamine to epoxy resin monomer is 1-2: 1. The molar ratio of furfurylamine to epoxy resin monomer can be 1: 1, 1.5: 1, 2: 1, etc.
[0026] In some embodiments, preferably, based on the total amount of the epoxy resin monomer, the amount of the quaternary ammonium salt catalyst is 0.5-1.5wt%. The amount of the quaternary ammonium salt catalyst affects the catalytic reaction time and yield, and the amount of the quaternary ammonium salt catalyst can be 0.5wt%, 1wt%, 1.5wt% of the amount of the epoxy resin monomer, etc.
[0027] In some embodiments, preferably, the quaternary ammonium salt catalyst is tetrabutylammonium bromide.
[0028] In some embodiments, preferably, the epoxy equivalent of the epoxy resin monomer is 182-192 g / eq.
[0029] In some embodiments, preferably, the temperature of the second reaction is 90-110° C. The temperature of the second reaction can be 90° C., 100° C., 110° C., etc., and the reaction time is 1-3 h, such as 1 h, 2 h, 3 h, etc.
[0030] In some embodiments, preferably, the third reaction temperature is 100-120°C, and the time is 1-3h. The third reaction temperature can be 100°C, 110°C, 120°C, etc., and the time can be 1h, 2h, 3h, etc.
[0031] In some embodiments, preferably, the preparation method of the modified curing agent comprises: dissolving maleic anhydride and 4'4-diaminodiphenyl disulfide separately and independently in a second solvent, adding the second solvent containing the 4'4-diaminodiphenyl disulfide dropwise into the second solvent containing the maleic anhydride, reacting at 80-100° C. for 1-3 hours, then sequentially adding a dehydrating agent, an acid binding agent and a metal nickel salt catalyst to continue the reaction for 2-4 hours, and removing the second solvent to obtain the modified curing agent.
[0032] The present invention has no special requirements for the type of the second solvent, as long as it can dissolve the corresponding compounds and does not produce any reaction. For example, the second solvent can be N,N-dimethylformamide.
[0033] The reaction temperature for preparing the modified curing agent can be 180°C, 90°C, 100°C, etc., the time for the first reaction can be 1h, 2h, 3h, etc., and the time for the continued reaction can be 2h, 3h, 4h, etc.
[0034] The process of removing the second solvent includes: placing the reaction product in a rotary evaporator, taking it out after rotary evaporation until no liquid drops, dissolving the residue in chloroform, and then washing it with a saturated sodium hydroxide solution several times (such as 3 times), and finally filtering the above chloroform solution with an organic filter membrane (pore size 0.22 μm), and vacuum drying the filtered residue at 60° C. for 6 hours to obtain the modified curing agent.
[0035] In some embodiments, preferably, the molar ratio of 4'4-diaminodiphenyl disulfide to maleic anhydride is 1:1-2. The molar ratio of 4'4-diaminodiphenyl disulfide to maleic anhydride can be 1:1, 1:1.5, 1:2, etc.
[0036] In some embodiments, preferably, based on the total amount of the maleic anhydride, the amount of the dehydrating agent is 15-25 wt %. The amount of the dehydrating agent can be 15 wt %, 20 wt %, 25 wt % of the mass of the maleic anhydride, etc.
[0037] In some embodiments, preferably, based on the total amount of maleic anhydride, the amount of the acid binding agent is 90-110 wt %. The amount of the acid binding agent can be 90 wt %, 100 wt %, 110 wt % of the mass of maleic anhydride, etc.
[0038] In some embodiments, preferably, based on the total amount of maleic anhydride, the amount of the metal nickel salt catalyst is 3-5 wt %. The metal nickel salt catalyst can be 3 wt %, 4 wt %, 5 wt % of the mass of maleic anhydride, etc.
[0039] In some embodiments, preferably, the dehydrating agent is acetic anhydride.
[0040] In some embodiments, preferably, the acid binding agent is triethylamine.
[0041] In some embodiments, preferably, the metal nickel salt catalyst is nickel acetate tetrahydrate.
[0042] A second aspect of the present invention provides a self-repairing epoxy glass material, which is prepared according to the preparation method described in the first aspect of the present invention.
[0043] The reaction principle of the present invention is specifically as follows:
[0044] like Figure 1 As shown, epoxy resin monomer (EP), suberic acid (SA) and furfurylamine (FA) react in the presence of a quaternary ammonium salt catalyst to obtain an epoxy resin copolymer.
[0045] Maleic anhydride (MA) and 4'4-diaminodiphenyl disulfide (4-AFD) react in the presence of a metal nickel salt catalyst to obtain a modified curing agent.
[0046] The epoxy resin copolymer and the modified curing agent react in the presence of an organic acid catalyst to obtain a self-repairing epoxy glass material, the network structure of which is as follows: Figure 1 As shown, from Figure 1 It can be seen that there are multiple functional bonds in the prepared material, including DA bonds, ester bonds, disulfide bonds, etc.
[0047] When the material is damaged, its network structure is destroyed. At this time, heating (80-160℃) can make the damaged material re-crosslinked, that is, self-repair can be achieved. The process is as follows Figure 2 As shown in the figure, it can be seen that the material becomes a chain structure after being destroyed. After heating, the ester bonds (green and purple parts), disulfide bonds (orange-red parts) and DA bonds (yellow parts) in the chain structure are broken and reconnected with each other.
[0048] The preparation method provided by the present invention, during the curing process, a cross-linking reaction occurs, specifically, the furan group of the epoxy resin copolymer and the maleimide group of the modified curing agent undergo a "click" reaction to quickly form an epoxy glass network polymer. The present invention utilizes the exchange effect of the formed DA bond, the ester bond of the epoxy resin copolymer itself, and the disulfide bond of the modified curing agent itself, so that the network topology of the epoxy glass material changes and rearranges under thermal stimulation, and the self-repair, reprocessing and shape memory functions of the polymer can be achieved. Since these three thermally reversible covalent bonds can be exchanged at different temperatures, the epoxy glass material provided by the present invention has a wide repair temperature, and self-repair can be achieved at 80-160°C.
[0049] In addition, the ester bonds and hydroxyl groups formed by the reaction of active groups will form hydrogen bonds in the network, effectively improving the mechanical properties of epoxy glass polymer materials.
[0050] The self-repairing epoxy glass material provided by the present invention has high self-repairing efficiency and short self-repairing time; and the raw materials for the preparation of the self-repairing epoxy glass material in the present invention are widely available, and the formula is flexible and changeable. The raw material ratio (such as the molar ratio of epoxy resin monomer to suberic acid) can be adjusted according to actual needs to regulate the mechanical properties of the material, and can be recycled and reused under certain conditions to reduce environmental pollution. Aromatic disulfide bonds are introduced in the present invention, and the aromatic disulfide exchange reaction does not require other additional stimulations and can be carried out under mild conditions or even at room temperature. Moreover, the material molecular chain in the present invention contains a small amount of hydroxyl groups, which is easy to form hydrogen bonds between molecular chains, which has an enhancing effect on the strength of the material. The present invention combines the thermally reversible characteristics of aromatic disulfide bonds, DA bonds, and ester bonds, so that the self-repairing epoxy glass material has a certain degree of repair ability at the disulfide exchange reaction temperature (80°C or even at room temperature), DA reaction temperature (about 80°C for the forward reaction and about 130°C for the reverse reaction), and ester exchange reaction temperature (about 150°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is the synthesis route diagram of Example 1 and the network structure diagram of the obtained material;
[0052] Figure 2This is a schematic diagram of the dynamic covalent bond (disulfide bond, ester bond, DA bond) exchange reaction of the material prepared in Example 3;
[0053] Figure 3 is a bar graph of tensile strength, fracture strain and toughness values of self-healing epoxy-type glass material samples (with different epoxy resin matrix / suberic acid ratios) from Examples 1-6;
[0054] Figure 4 is a bar graph of tensile strength, fracture strain and toughness values of self-healing epoxy-type glass material samples (with different ratios of epoxy resin copolymer / modified curing agent) from Examples 7-10;
[0055] Figure 5 It is a bar graph of the tensile strength, fracture strain and toughness values of the self-repairing epoxy glass material sample in Example 3 under different repair conditions.
[0056] Figure 6 These are optical microscope photos of the self-repairing epoxy glass material samples in Example 3 under different repair conditions. DETAILED DESCRIPTION
[0057] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. The terms "first", "second", etc. are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally a class, and the number of objects is not limited. For example, the first object can be one or more.
[0058] In addition, the term "and / or" in the specification and claims is used to describe the association relationship of associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the objects associated before and after are in an "or" relationship. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more. In the description of this specification, the description of the reference terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
[0059] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0060] The raw materials used in the following examples and comparative examples, unless otherwise specified, are commercially available products well known in the art.
[0061] Epoxy resin monomer, its structural formula is: Its epoxy equivalent is 185 g / eq.
[0062] The tensile strength was measured using the GB / T1040.2-2008 method;
[0063] The fracture strain was measured using the GB / T1040.2-2008 method;
[0064] Toughness is obtained by calculating the enclosed area of the specimen.
[0065] According to the stress (σ)-strain (ε) curve, using the formula:
[0066]
[0067] Where τ is the toughness of the sample, ε is the strain of the sample, σ is the stress of the sample, and ε max is the elongation of the sample when it breaks.
[0068] Tensile strength repair rate = tensile strength of the material after self-repair / tensile strength of the material before damage × 100%;
[0069] Fracture strain repair rate = fracture strain of the material after self-repair / fracture strain of the material before being damaged × 100%;
[0070] Toughness value repair rate = toughness value of the material after self-repair / toughness value of the material before being damaged × 100%.
[0071] Example 1
[0072] S100, preparing an epoxy resin copolymer, specifically as follows:
[0073] Weigh furfurylamine and epoxy resin monomer according to a molar ratio of 2:1 for later use;
[0074] The epoxy resin monomer is stirred in an ice bath under nitrogen protection until it is completely dissolved in toluene, the furfurylamine is added dropwise and the temperature is rapidly raised to 110° C., and the reaction is condensed and refluxed for 2 hours. The obtained product is then placed in a rotary evaporator and evaporated until no liquid drops. The remaining product is the epoxy resin copolymer.
[0075] S200, preparing a modified curing agent, as follows:
[0076] (1) weighing 4',4-diaminodiphenyl disulfide and maleic anhydride in a molar ratio of 1:2 for later use;
[0077] (2) completely dissolving the maleic anhydride in N,N-dimethylformamide, and heating to 90° C., completely dissolving the 4'4-diaminodiphenyl disulfide in N,N-dimethylformamide, and then adding the 4'4-diaminodiphenyl disulfide dropwise into the N,N-dimethylformamide containing maleic anhydride, and maintaining the temperature at 90° C. and stirring for 2 h;
[0078] (3) adding acetic anhydride, triethylamine and nickel acetate tetrahydrate to the reaction of step (2) in sequence, maintaining the temperature and stirring the reaction for 3 hours, wherein the amounts of acetic anhydride, triethylamine and nickel acetate tetrahydrate added are 15wt%, 100wt% and 3wt% of the mass of maleic anhydride, respectively;
[0079] (4) placing the product of step (3) in a rotary evaporator, evaporating until no liquid is left, then taking out the product, dissolving the residue in chloroform, and then washing it three times with a saturated sodium hydroxide solution, and finally filtering the solution with an organic filter membrane (pore size of 0.22 μm);
[0080] (5) The residue after filtration in step (4) was dried under vacuum at 60° C. for 6 h to obtain a modified curing agent.
[0081] S300, preparing a self-repairing epoxy glass material, specifically as follows:
[0082] Weigh the epoxy resin copolymer and anhydrous zinc acetate at a molar ratio of 10:0.5, and weigh the epoxy resin copolymer and the modified curing agent at a molar ratio of 2:1 for later use;
[0083] The epoxy resin copolymer and anhydrous zinc acetate are heated and mixed at 105° C. for 1 hour until the anhydrous zinc acetate is completely dissolved to obtain a resin mixture, and then the resin mixture is cooled to 80° C., the modified curing agent is added, and after stirring evenly, vacuum stirring is performed at 80° C. to remove bubbles, and the mixture is further cured at 80° C. for 1 hour, and then the temperature is raised to 150° C. for curing for 2 hours to obtain a self-repairing epoxy glass material.
[0084] Example 2
[0085] S100, preparing an epoxy resin copolymer, specifically as follows:
[0086] (1) Weighing furfurylamine and epoxy resin monomer in a molar ratio of 2:1, weighing epoxy resin monomer and suberic acid in a molar ratio of 10:1, and weighing tetrabutylammonium bromide in an amount of 1 wt % of the mass of the epoxy resin monomer for later use;
[0087] (2) at 105° C., the epoxy resin monomer and the suberic acid are reacted with tetrabutylammonium bromide to cause an epoxy ring opening reaction with the carboxylic acid to produce an epoxy end-capped β-hydroxy ester epoxy resin, and the reaction time is 2 hours;
[0088] (3) The product of step (2) was stirred in an ice bath under nitrogen protection until it was completely dissolved in toluene, the furfurylamine was added dropwise and the temperature was quickly raised to 110° C., and the reaction was condensed and refluxed for 2 h;
[0089] (4) The product of step (3) is placed in a rotary evaporator and evaporated until no liquid drops, and the remaining product is the epoxy resin copolymer.
[0090] S200, preparing a modified curing agent, as follows:
[0091] (1) weighing 4',4-diaminodiphenyl disulfide and maleic anhydride in a molar ratio of 1:2 for later use;
[0092] (2) completely dissolving the maleic anhydride in N,N-dimethylformamide, and heating to 90° C., completely dissolving the 4'4-diaminodiphenyl disulfide in N,N-dimethylformamide, and then adding the 4'4-diaminodiphenyl disulfide dropwise into the N,N-dimethylformamide containing maleic anhydride, and maintaining the temperature at 90° C. and stirring for 2 h;
[0093] (3) adding acetic anhydride, triethylamine and nickel acetate tetrahydrate to the reaction of step (2) in sequence, maintaining the temperature and stirring the reaction for 3 hours, wherein the amounts of acetic anhydride, triethylamine and nickel acetate tetrahydrate added are 15wt%, 100wt% and 3wt% of the mass of maleic anhydride, respectively;
[0094] (4) placing the product of step (3) in a rotary evaporator, evaporating until no liquid is left, taking out the product, dissolving the residue in chloroform, and then washing it three times with a saturated sodium hydroxide solution, and finally filtering the solution with an organic filter membrane (pore size of 0.22 μm);
[0095] (5) The residue after filtration in step (4) was dried under vacuum at 60° C. for 6 h to obtain a modified curing agent.
[0096] S300, preparing a self-repairing epoxy glass material, specifically as follows:
[0097] Weigh the epoxy resin copolymer and anhydrous zinc acetate at a molar ratio of 10:0.5, and weigh the epoxy resin copolymer and the modified curing agent at a molar ratio of 2:1 for later use;
[0098] The epoxy resin copolymer and anhydrous zinc acetate are heated and mixed at 105° C. for 1 hour until the anhydrous zinc acetate is completely dissolved to obtain a resin mixture, and then the resin mixture is cooled to 80° C., the modified curing agent is added, and after stirring evenly, vacuum stirring is performed at 80° C. to remove bubbles, and the mixture is further cured at 80° C. for 1 hour, and then the temperature is raised to 150° C. for curing for 2 hours to obtain a self-repairing epoxy glass material.
[0099] Example 3
[0100] The method of Example 2 was followed, except that the molar ratio of the epoxy resin monomer to suberic acid was 10:2.
[0101] Example 4
[0102] The method of Example 2 was followed, except that the molar ratio of the epoxy resin monomer to suberic acid was 10:3.
[0103] Example 5
[0104] The method of Example 2 was followed, except that the molar ratio of the epoxy resin monomer to suberic acid was 10:4.
[0105] Example 6
[0106] The method of Example 2 was followed, except that the molar ratio of the epoxy resin monomer to suberic acid was 10:5.
[0107] Example 7
[0108] The method of Example 3 was followed, except that the molar ratio of the epoxy resin copolymer to the modified curing agent was 2:0.5.
[0109] Example 8
[0110] The method of Example 3 was followed, except that the molar ratio of the epoxy resin copolymer to the modified curing agent was 2:1.5.
[0111] Example 9
[0112] The method of Example 3 was followed, except that the molar ratio of the epoxy resin copolymer to the modified curing agent was 2:2.
[0113] Example 10
[0114] The process was carried out in the same manner as in Example 3, except that the molar ratio of the epoxy resin copolymer to the organic acid catalyst was 10:1.25.
[0115] Embodiment 11
[0116] The process was carried out in the same manner as in Example 3, except that the molar ratio of the epoxy resin copolymer to the organic acid catalyst was 10:2.5.
[0117] Example 12
[0118] The process was carried out in the same manner as in Example 3, except that the resin mixture and the modified curing agent were first reacted at 60° C. for 2 h, and then the temperature was raised to 180° C. and the reaction was continued for 1 h.
[0119] Example 13
[0120] The process was carried out in the same manner as in Example 3, except that the resin mixture and the modified curing agent were first reacted at 100° C. for 0.5 h, and then the temperature was raised to 130° C. and the reaction was continued for 3 h.
[0121] Embodiment 14
[0122] The process was carried out in the same manner as in Example 3, except that the resin mixture and the modified curing agent were first reacted at 120° C. for 1 h, and then the temperature was raised to 200° C. for further reaction for 2 h.
[0123] Embodiment 15
[0124] The process was carried out in the same manner as in Example 3, except that the resin mixture and the modified curing agent were first reacted at 50° C. for 1 h, and then the temperature was raised to 100° C. for further reaction for 2 h.
[0125] Example 16
[0126] The process was carried out in the same manner as in Example 3, except that the molar ratio of 4'4-diaminodiphenyl disulfide to maleic anhydride was 1:4.
[0127] Embodiment 17
[0128] The method of Example 3 was followed, except that the molar ratio of 4'4-diaminodiphenyl disulfide to maleic anhydride was 1:0.5.
[0129] Embodiment 18
[0130] The method of Example 3 was followed, except that the molar ratio of the epoxy resin copolymer to the modified curing agent was 2:5.
[0131] Embodiment 19
[0132] The process was carried out in the same manner as in Example 3, except that the molar ratio of the epoxy resin copolymer to the organic acid catalyst was 20:10.
[0133] The materials prepared in Examples 1-9 were used as test objects to test their tensile strength, fracture strain, toughness, etc. The test results are as follows: Figure 3 (materials from Examples 1-6) and 4 (materials from Examples 3 and 7-9).
[0134] Depend on Figure 3 It can be seen that when the ratio of epoxy resin monomer to suberic acid is 10:2, the obtained material exhibits strong and tough characteristics, and the overall performance is optimal. As the proportion of suberic acid continues to increase, the fracture strain of the self-healing glass material gradually increases, and the tensile strength and toughness continue to decrease. Analyzing the reasons, the epoxy resin monomer has a rigid structure with a benzene ring, which improves the strength of the material; the presence of hydrogen bonds increases the interaction force between molecules, making it more difficult for the molecular chain to slip relative to each other when subjected to force, thereby effectively improving the material's ability to resist deformation and thus improving mechanical strength. At the same time, the hydrogen bond network can, to a certain extent, play a role in energy dissipation when the material is impacted by external forces, further enhancing the toughness of the material. Suberic acid acts as a dynamic soft segment, improving the toughness of the material, and excessive suberic acid leads to a decrease in the strength of the material.
[0135] Depend on Figure 4 It can be seen that the epoxy resin copolymer / modified curing agent (2:1) exhibits strong and tough characteristics, and the overall performance is optimal. As the proportion of modified curing agent continues to increase, the tensile strength, fracture strain and toughness of the self-healing glass material continue to decrease. Analyzing the reasons, the modified curing agent in the cross-linked network contains disulfide bonds and DA bonds, which act as dynamic hard segments. As the content of modified curing agent increases, the disulfide bonds are weak bonds and are easy to break, forming a soft network structure, which continuously reduces its mechanical properties.
[0136] The self-healing performance of the material prepared in Example 3 (the molar ratio of epoxy resin monomer / sucrose acid is 10:2, and the molar ratio of epoxy resin copolymer / modified curing agent is 2:1) is further tested. The specific method is as follows: a scratch treatment is performed on the material sample, and the scratch width is about 46 μm. The material sample is placed under an optical microscope equipped with a heating stage and heated to 80°C, 130°C, and 150°C, respectively, and the scratch repair is observed.
[0137] like Figure 5 and 6 As shown, the material prepared in Example 3 is basically healed after 300 minutes at 80°C; basically healed after 75 minutes at 130°C; and basically healed after 75 minutes at 150°C.
[0138] The mechanical properties of the samples were tested after repair. The strips were completely cut in the middle and the fracture surfaces were aligned and pressed tightly together. They were heated and placed for a period of time. Reversible dynamic covalent bond (DA bond, disulfide bond and ester bond) exchange reactions occurred between the pressed sections, achieving network rearrangement and thus repairing the sections.
[0139] Depend on Figure 5 It can be seen that the self-healing effect is best under the conditions of 150°C and 75 minutes. The tensile strength of the material after self-healing is 55.76MPa, the fracture strain is 50.28%, and the toughness value is 18.16MJ / m 3 ; Calculation shows that the tensile strength repair rate is 89%, the fracture strain repair rate is 89.61%, and the toughness value repair rate is 84.43%.
[0140] The tensile strength, fracture strain and toughness of the materials obtained in Examples 1-19 were tested, and their mechanical properties were further tested after a self-repair test at 150°C for 75 min, and their repair rates were calculated. The specific results are shown in Table 1.
[0141] Table 1 Self-healing properties of materials
[0142]
[0143] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a self-repairing epoxy glass material, characterized in that: The preparation method comprises: subjecting an epoxy resin copolymer, a modified curing agent and an organic acid catalyst to a first reaction, wherein the molar ratio of the epoxy resin copolymer to the modified curing agent is 2:0.5-5, and the molar ratio of the organic acid catalyst to the epoxy resin copolymer is 1-10:
20.
2. The preparation method according to claim 1, wherein The first reaction process includes: mixing the epoxy resin copolymer and an organic acid catalyst to obtain a resin mixture; Add the modified curing agent to the resin mixture, react at 60-100° C. for 0.5-2 hours, then heat to 130-180° C. and continue to react for 1-3 hours; And / or, the organic acid catalyst is anhydrous zinc acetate.
3. The preparation method according to claim 1 or 2, wherein The molar ratio of the epoxy resin copolymer to the modified curing agent is 2:
1.
4. The preparation method according to any one of claims 1 to 3, wherein The preparation method of the epoxy resin copolymer comprises: performing a third reaction on an epoxy resin monomer and furfurylamine to obtain the epoxy resin copolymer; Or, the preparation method of the epoxy resin copolymer comprises: conducting a second reaction of epoxy resin monomer and suberic acid in the presence of a quaternary ammonium salt catalyst to obtain an epoxy group-terminated β-hydroxy ester-containing epoxy resin; The β-hydroxy ester-containing epoxy resin is dissolved in a first solvent, and furfurylamine is added to carry out a third reaction, and the first solvent is removed to obtain an epoxy resin copolymer.
5. The preparation method according to claim 4, wherein The molar ratio of the epoxy resin monomer to suberic acid is 10:0.1-5; and / or, the molar ratio of furfurylamine to epoxy resin monomer is 1-2:1; and / or, based on the total amount of the epoxy resin monomer, the amount of the quaternary ammonium salt catalyst is 0.5-1.5wt%; And / or, the quaternary ammonium salt catalyst is tetrabutylammonium bromide; And / or, the epoxy equivalent of the epoxy resin monomer is 182-192 g / eq.
6. The preparation method according to claim 5, wherein: The molar ratio of the epoxy resin monomer to suberic acid is 10:
2.
7. The preparation method according to any one of claims 4 to 6, wherein: The temperature of the second reaction is 90-110°C; Preferably, the third reaction temperature is 100-120° C., and the time is 1-3 h.
8. The preparation method according to any one of claims 1 to 7, wherein: The preparation method of the modified curing agent comprises: dissolving maleic anhydride and 4'4-diaminodiphenyl disulfide in a second solvent respectively and independently, adding the second solvent containing the 4'4-diaminodiphenyl disulfide dropwise into the second solvent containing the maleic anhydride, reacting at 80-100° C. for 1-3 hours, then sequentially adding a dehydrating agent, an acid binding agent and a metal nickel salt catalyst to continue reacting for 2-4 hours, and removing the second solvent to obtain the modified curing agent.
9. The preparation method according to claim 8, wherein: The molar ratio of 4'4-diaminodiphenyl disulfide to maleic anhydride is 1:1-2; and / or, based on the total amount of the maleic anhydride, the amount of the dehydrating agent is 15-25wt%; and / or, based on the total amount of the maleic anhydride, the amount of the acid binding agent is 90-110wt%; and / or, based on the total amount of the maleic anhydride, the amount of the metal nickel salt catalyst is 3-5wt%; And / or, the dehydrating agent is acetic anhydride; And / or, the acid binding agent is triethylamine; And / or, the metal nickel salt catalyst is nickel acetate tetrahydrate.
10. A self-repairing epoxy glass material, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Self-repairing material preparing method based on duplex repairing mechanism
CN110105544A
Self-repairing heat-conducting epoxy resin composite material and preparation method and application thereof
CN112210194A
High-performance self-repairing epoxy resin and preparation method thereof
CN116694026A
Cited By
Organic glass scintillator material and preparation method and application thereof
CN121930442A